Pancasila di Era Society 5.0 : Menjadi Generasi Sehat, Beretika, dan Inspiratif - Ashoka Rahma Ramadani; Naia Arlyn Shafina Adzra; Putri Aulia Rahmah; Zakia Sabila Haq; Supriyono (Jurnal Pendidikan UNIGA, 2026)
Technological developments in the Society 5.0 era have brought about major changes in human life, especially for the younger generation. Advances in digital technology have influenced communication patterns, learning methods, and even the way moral values are interpreted in everyday life. On one hand, technology provides many conveniences, but on the other hand, it also poses challenges in the form of a rapid flow of information, shifting social values, and the potential for ethical deviations in the digital space. In these circumstances, Pancasila plays a very important role as a guideline for life in shaping the character of the younger generation to be healthy, ethical, and inspiring. This study aims to explain the urgency of Pancasila in the Society 5.0 era and identify how the younger generation practices the values of Pancasila in their daily lives. The method used is a descriptive qualitative approach with data collection techniques in the form of distributing questionnaires to 51 participants and studying literature from various relevant sources. The results of the study show that most students view the values of Pancasila as still relevant and very much needed as guidelines for behavior and interaction, both in the real world and in the digital space. The novelty of this research lies in the integration of digital literacy and self-efficacy in predicting the urgency of Pancasila in the era of society 5.0, which has previously been studied more extensively among university students. The implications of this research emphasize the practice of Pancasila values in daily life in order to be prepared to face the challenges of the era of society 5.0.